COMPREHENSIVE SEXUAL EDUCATION AND CHILDHOOD: ISSUES RAISED IN BRAZILIAN STUDIES WITHIN THE LATIN CARIBBEAN CONTEXT - Claudionor Renato da Silva (Universidad Nacional del Nordeste, 2021)
Comprehensive Sexual Education (CSE) is not a recurring term within current studies in the area of Sexual Education in Brazil. In terms of the RIIE proposal's initiative, this essay-based study problematizes CSE in Brazilian Early Childhood Education; in the first place, by trying to understand why the terminology/ conceptualization/methodology (education policies and actions) are absent in national productions. The argumentative answers to the problematization are found in the historical rescue of the extinct RCNEI of the 1990s, which can be considered a CSE policy. As a guideline, this paper postulates that one of the ways of reflecting upon the "problematization" of Brazilian studies is to think about the foundations of Comprehensive Education as one of the first actions on Childhood Education within the context of Latin America and the Caribbean (LA and Ca). The study concludes by advocating for a greater dialogue/partnership of Brazilian researchers with researchers of research centers in LA and the Ca, including the active coordination with social movements and political parties from Brazilian cities to the State and the federal levels, so as to formulate public policies on CSE in Early Childhood Education.